Local Beef Cattle Breeding Program in Indonesia - Endang Romjali (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2018)
Indonesia has a number of cattle breeds that have certain advantages as meat-producing cattle with high adaptability to the local environment. Local beef cattle breeding has now been carried out by the government through technical implementation unit. Efforts to build local cattle breeding still need to be improved to be able to meet sustainably the demands of local cattle breeding stocks for the farmers. However, beef cattle breeding business is less attractive to investors because it is economically less profitable and requires a long maintenance time compared to the fattening business. This paper aims to provide an overview of thoughts in an effort to improve the performance of local beef cattle breeding in Indonesia. In supporting the local cattle breeding program, the role of central and regional governments still has to be dominant mainly in the establishing of breeding centers as the core and policies related to the operationalization of activities involving farmers and other stakeholders.